PENDIDIKAN AGAMA ISLAM PADA MASA KOLONIAL HINGGA AWAL KEMERDEKAAN INDONESIA - Héctor Javier Cortés Tornel; Faridi (An-Nahdlah: Jurnal Pendidikan Islam, 2026)
Islamic Religious Education (Pendidikan Agama Islam/PAI) during the colonial period and the early years of Indonesian independence developed as part of broader social dynamics shaped by the relationship between colonial power, society, and religion. Marginalized from the formal colonial education system, Islamic education grew through pesantren and the role of Islamic educational actors outside state control. This article examines the dynamics of PAI in Indonesian society, the role of Islamic institutions and figures in responding to colonial education, and the transformation of PAI’s orientation during the transition to independence. Employing a qualitative library-based method and a social-historical approach, the study finds that the marginalization of PAI was rooted in its ideological and social independence rather than institutional backwardness. During the period of national awakening and early independence, PAI contributed to ethical formation, social solidarity, and national consciousness, while gradually shifting from religious community education toward citizenship-oriented education.